An examination of the deliberate practice framework in quad rugby - Kennedy, R. L.; Fairbrother, J. T. (Frontiers in Psychology, 2019)
The deliberate practice framework was forwarded to account for the characteristics and developmental experiences of individuals who have acquired exceptional performance in any domain. This framework proposed that experts undergo an extensive acquisition period involving the accumulation of thousands of hours of deliberate practice while overcoming various constraints that serve as functional barriers to the achievement of expertise. Although the deliberate practice framework has been examined in the context of a range of domains, disability sport remains relatively unstudied. The purpose of this study was, therefore, to examine expert disability sport athletes to determine how well their experiences and characteristics were captured by the deliberate practice framework. Quad rugby players were asked to complete a two-part survey to report their recall of the amount of time spent in individual and team practice activities, quad rugby related activities, and daily life activities at the start of their careers and every 2 years since. These activities were then rated with respect to relevance to improving performance, effort and concentration required, and enjoyment of participation. Findings revealed that quad rugby athletes engaged in similar amounts of practice throughout their career to those observed in superior performers across domains, including musicians and expert performers in the able-bodied sport domain (e.g., M = 8,309 h at 9-10 year career mark). Contrary to the original deliberate practice framework and some of the subsequent examinations in sport, disability sport athletes did not rate the most relevant and effortful activities as either low or high on enjoyment. The unique constraints imposed on disabled athletes may reduce the likelihood that clear differences will emerge when considering affective responses such as enjoyment.